The Effectiveness of Video Education on the Knowledge of Pregnant Women about Neonatal Danger Signs - Nunung Zubaidah; Siti Chunaeni; Arum Lusiana (Poltekkes Kemenkes Semarang, 2022)
Background: The neonatal danger signs are a group of symptom presented in sick neonates that can. The Infant Mortality Rate (IMR) is calculated from the number of infant deaths 0